Optimal therapeutic strategies for pineal region lesions - Huang, Li-tian; Wang, Chun-xi; Li, Tang; Wang, Sheng-yong; Zhou, Quan; Tong, Xiaoguang (Frontiers in Neurology, 2023)
Background The removal of pineal region lesions are challenging, and therapeutic strategies for their removal remain controversial. The current study was conducted to identify the characteristics and the optimal therapeutic strategies for pineal region lesions. Methods This retrospective study reviewed the treatments of 101 patients with pineal region lesions, and different characteristics and therapeutic strategies were observed. Results There were no statistical differences in the total resection ratio, complications, and prognosis outcomes between the hydrocephalus group and non-hydrocephalus group, except patients in the hydrocephalus group were younger and pediatric patients had an increased level of intracranial infections. Treatments of lesions and hydrocephalus secondary to pineal region lesions were two integral parts to therapeutic strategies. For the management of lesions, germinoma or non-germinoma were diagnosed preoperatively, and resection or diagnostic radiation were chosen to deal with pineal region lesions. Endoscopic-assisted surgery provided a higher total resection rate. For the management of hydrocephalus, endoscopic third ventriculostomy (ETV) had the better therapeutic effect. Additionally, cerebrospinal fluid (CSF) diversion before radiotherapy or resection did not improve prognosis outcome, but it was necessary for patients with severe hydrocephalus. Logistical regression analysis indicated that age, lesion size, reoperation ratio, and intracranial complications were predictors of prognosis outcome. Conclusion More attention should be paid to intracranial infections in pediatric patients with hydrocephalus secondary to pineal region lesions, and CSF diversion before radiotherapy or resection did not promote prognosis outcome, but it was necessary for patients with severe hydrocephalus. Age, lesion size, reoperation ratio, and intracranial complications may be the predictors of prognosis outcome. Most importantly, the surgical algorithm for pineal region lesions which was based on preoperatively diagnosis (non-germinoma and germinoma) is useful, especially for developing countries.